Victoria - Travelog Publications (Firm) (North Ryde, N.S.W. : Travelog Publications, 1986)
Special points of tourist interest given. Map shows state forests and national, state & historic parks.
On verso: Information on the Garden State -- National Parks with location and information.
Keywords: Victoria -- Maps; Tourist maps